Development of antibodies against the Notch pathway ligand JAG1 using phage display technology - Marques, Gonçalo Rodrigues Puidival (2019)
The Notch signaling pathway is a cell-to-cell communication system that plays crucial roles during the embryonic development and in the tissue homeostasis. In mammals, this pathway is constituted by four Notch receptors (Notch1-4) and five Notch ligands (DLL1, 3 and 4, and JAG1 and 2). Binding of the ligands to the receptors in adjacent cells leads to the activation of the Notch pathway and the regulation of a multitude of genes that control many cellular processes such as stem cell self-renewal, cell differentiation, proliferation, and survival. Deregulated expression of Notch signaling components are observed in many cancers, including breast, and shown to be implicated in tumor growth, recurrence and drug resistance. JAG1 is one of the five Notch ligands that is overexpressed in aggressive cancers and mediates many of the Notch signaling tumorigenic functions. JAG1 overexpression promotes cancer cell survival, proliferation, migration, metastasis, cancer stem cell population maintenance, tumor-associated angiogenesis, and allows tumor cells to escape the immune surveillance. The goal of this work was to develop specific anti-JAG1 antibodies using phage display technology. To achieve that we used the Human Single Fold scFv Tomlinson library I+J and recombinant JAG1-EGF3-Fc protein as antigen. After several rounds of selections, 84 scFv clones capable to recognize and bind to recombinant JAG1 proteins were isolated. The binding of the 84 scFvs towards the JAG1 was tested by ELISA assays using recombinant JAG1 proteins. Additionally, the binding of anti-JAG1 scFvs to endogenous cellular JAG1 was tested by flow cytometry. Sequencing analysis of the selected clones allowed the identification of 19 unique anti-JAG1 scFvs. One was reformatted into two anti-JAG1 IgGs: one with a glycosite in HCDR2 and the other without. These IgG molecules were characterized by ELISA and SDS-PAGE, and our data showed that after reformatting they were no longer able to recognize JAG1.